Computer media and communication a reader - Mayer, Paul A (Ed.) (Oxford Oxford University Press, 1999)
Computer media and communication-A Reader is a collection of key texts about computer and media.The book is divided into two parts: The first part offer a chronological overview of how thinking about computers as a means of communication developed; while
Keywords: Telematics; Telecommunication; Computers